Hydra has mammal-like mutation rates facilitating fast adaptation despite its nonaging phenotype - Sahm, Arne; Riege, Konstantin; Groth, Marco; Bens, Martin; Kraus, Johann; Fischer, Martin; Kestler, Hans; Englert, Christoph; Schaible, Ralf; Platzer, Matthias; Hoffmann, Steve (Genome Research, 2024)
Growing evidence suggests that somatic mutations may be a major cause of the aging process. However, it remains to be tested whether the predictions of the theory also apply to species with longer life spans than humans. Hydra is a genus of freshwater polyps with remarkable regeneration abilities and a potentially unlimited life span under laboratory conditions. By genome sequencing of single cells and whole animals, we found that the mutation rates in Hydra’s stem cells are even slightly higher than in humans or mice. A potential explanation for this deviation from the prediction of the theory may lie in the adaptability offered by a higher mutation rate, as we were able to show that the genome of the widely studied Hydra magnipapillata strain 105 has undergone a process of strong positive selection since the strain's cultivation 50 years ago. This most likely represents a rapid adaptation to the drastically altered environmental conditions associated with the transition from the wild to laboratory conditions. Processes under positive selection in captive animals include pathways associated with Hydra’s simple nervous system, its nucleic acid metabolic process, cell migration, and hydrolase activity.
10.1101/gr.279025.124